Virtual reality in lighting research: Comparing physical and virtual lighting environments. (October 2019) - Chen, Y; Cui, Z; Hao, L
In the study of lighting, as the construction of a physical test room is costly and time-consuming, researchers have been actively looking for alternative media to present physical environments. Virtual reality, photo and video are the most commonly used approaches in the lighting community, and they have all been used by researchers around the world. Most such studies have been conducted without discussing what gives the subjects a better sense of realism, presence, etc., and which type of media is closer to the ideal, the physical lighting environment. In this paper, we aim to select the optimal alternative media that can present physical lighting environments. We compare a human's subjective feeling towards a physical lighting environment and three alternative reproduction technologies, namely, virtual reality reproduction, video reproduction and photographic reproduction. We also discuss the feasibility of using virtual reality in representing lighting environments. The selection of the most optimal media is based on the perceptual attributes of lighted space, and the findings are only related to these criteria. The main results of this study are the following: (a) The order of the overall presentation-ability of the media is physical space > virtual reality reproductions > video reproductions > photo reproductions. (b) In terms of subjective rating, virtual reality lighting environments are rated closest to the physical lighting environments, and the order of the approximate coefficient of the media is physical space (1) > VR reproductions (0.886) > video reproductions (0.752) > photo reproductions (0.679). (c) Virtual reality can present lighting attributes of open/close, diffuse/glaring, bright/dim and noisy/quiet consistent with the physical environment. (d) Human subjects are most satisfied with VR reproductions.